[Boat people ; New beginnings ; Kabuki - Lazaro, Cheche (The Probe Team, 1990)
Discusses the Vietnamese boat people rescued by a Canadian ship who took refuge in the Philippines. Also includes interviews with Vietnamese, Drug addicts and alcoholics taken care of in a house founded by Peter to Zobel in Paranaque.